Results and evaluation of the expansion of a model of comprehensive care for Chagas disease within the National Health System: The Bolivian Chagas network. - Maria-Jesus Pinazo; Mirko Rojas-Cortez; Ruth Saravia; Wilson Garcia-Ruiloba; Carlos Ramos; Jimy-Jose Pinto Rocha; Lourdes Ortiz; Mario Castellon; Nilce Mendoza-Claure; Daniel Lozano; Faustino Torrico; Joaquim Gascon; et al. (Public Library of Science (PLoS), 2022)
Background Most people with chronic Chagas disease do not receive specific care and therefore are undiagnosed and do not receive accurate treatment. This manuscript discusses and evaluates a collaborative strategy to improve access to healthcare for patients with Chagas in Bolivia, a country with the highest prevalence of Chagas in the world. Methods With the aim of reinforcing the Chagas National Programme, the Bolivian Chagas Platform was born in 2009. The first stage of the project was to implement a vertical pilot program in order to introduce and consolidate a consensual protocol-based healthcare, working in seven centers (Chagas Platform Centers). From 2015 on the model was extended to 52 primary healthcare centers, through decentralized, horizontal scaling-up. To evaluate the strategy, we have used the WHO ExpandNet program. Results The strategy has significantly increased the number of patients cared for, with 181,397 people at risk of having T. cruzi infection tested and 57,871 (31·9%) new diagnostics performed. In those with treatment criteria, 79·2% completed the treatment. The program has also trained a significant number of health personnel through the specific Chagas guidelines (67% of healthcare workers in the intervention area). Conclusions After being recognized by the Chagas National Programme as a healthcare model aligned with national laws and priorities, the Bolivian platform of Chagas as an innovation, includes attributes that they have made it possible to expand the strategy at the national level and could also be adapted in other countries.